THE REPRESENTATION OF CLASS STRUGGLE IN DETROIT FILM - Rizal Rachman Ally; Elisabeth Ngestirosa Endang Woro Kasih (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2021)
The study focuses on Detroit (2017) film that tells the story of a true event in Michigan, Detroit 1967. The film delineates the social conflict among White and Black community. The social issues that occur in this film, the researchers see this as a form of social problems related to Marxists. This study uses the Marxist class struggle theory and also uses Barthes' semiotics and cinematography to help researchers analyze research. Class struggle occurs because of conflicts between certain groups for their own interests to achieve freedom in social society. In this study, the data source is taken from Detroit 2017 film directed by Kathryn Bigelow produced in America distributed by Annapurna Pictures which becomes the primary data sources. The data collecting technique will be applied as the primary step in doing the research. All data will be collected using some steps to gather comprehensive data that will be meaningful for data analysis. Based on the results of the analysis of class struggle in Detroit (2017), the authors found that there were social conflicts that occurred in society. Class struggle occurs because of conflicts between certain groups for their own interests to achieve freedom in social society. The class struggle is depicted through scenes and dialogues in the film, in which the researcher sees a problem between the group of black people and white people.Keywords: Barthes, class conflict, class struggle, Marxist, semiotic